2019
DOI: 10.3390/metabo9070146
|View full text |Cite
|
Sign up to set email alerts
|

1H HR-MAS NMR-Based Metabolomics of Cancer Cells in Response to Treatment with the Diruthenium Trithiolato Complex [(p-MeC6H4iPr)2Ru2(SC6H4-p-But)3]+ (DiRu-1)

Abstract: The trithiolato bridged diruthenium complex DiRu-1 [(p-MeC6H4iPr)2Ru2(SC6H4-p-But)3]+ is highly cytotoxic against various cancer cell lines, but its exact mode of action remains unknown. The present 1H HR-MAS NMR-based metabolomic study was performed on ovarian cancer cell line A2780, on its cis-Pt resistant variant A2780cisR, and on the cell line HEK-293 treated with 0.03 µM and 0.015 µM of DiRu-1 corresponding to full and half IC50 doses, respectively, to investigate the mode of action of this ruthenium comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…This was ascribed in part to the activation of cellular anti-oxidative reactions through GSH synthesis compensating GSH loss [12,13]. Unlike cisPt, ruthenium-based surrogates [15,16] and other anti-cancer drugs [31] induced increased GSH levels in cisPt-sensitive A2780 cells upon treatment. Since these drugs are proposed to follow alternative cell death pathways other than DNA-damage, their GSH consumption may be reduced.…”
Section: Glutathione (Gsh)mentioning
confidence: 99%
See 1 more Smart Citation
“…This was ascribed in part to the activation of cellular anti-oxidative reactions through GSH synthesis compensating GSH loss [12,13]. Unlike cisPt, ruthenium-based surrogates [15,16] and other anti-cancer drugs [31] induced increased GSH levels in cisPt-sensitive A2780 cells upon treatment. Since these drugs are proposed to follow alternative cell death pathways other than DNA-damage, their GSH consumption may be reduced.…”
Section: Glutathione (Gsh)mentioning
confidence: 99%
“…In particular, the impact of cisPt on the metabolic profile of various cancer cell lines has been addressed by HR-MAS NMR-based chemometric analyses and has led to the identification of biomarkers for treatment response [12][13][14]. Recently, the metabolic alterations in cisPt sensitive and resistant A2780 cells following treatment with Ruthenium complexes as alternatives to cisPt were shown [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…13,19,21,22 Recent in vivo studies have demonstrated that these complexes indeed have potential as anticancer drugs, since for instance the compound [(h 6 -p-MeC 6 H 4 Pr i ) 2 Ru 2 (m 2 -S-p-C 6 H 4 Bu t ) 3 ]Cl (termed diruthenium-1) signicantly prolongs the survival of tumour-bearing mice 25 and substantially inuences metabolism of A2780cisR cells involving changes related to redox homeostasis, Warburg effect and lipid metabolism. 45 Other derivatives appear less promising. 44,46 Dinuclear thiolato-bridged arene ruthenium complexes are also promising as antiprotozoal agents, with IC 50 values of up to 1.2 nM against T. gondii, N. caninum and T. brucei and IC 50 values against human foreskin broblasts >800 mM, leading to selectivity indexes >20 000.…”
Section: Introductionmentioning
confidence: 99%
“…13,19,21,22 Recent in vivo studies have demonstrated that these complexes indeed have potential as anticancer drugs, since for instance the compound [(η 6 -p-MeC6H4Pr i )2Ru2(µ2-S-p-C6H4Bu t )3]Cl (termed diruthenium-1) significantly prolongs the survival of tumour-bearing mice 25 and substantially influences metabolism of A2780cisR cells involving changes related to redox homeostasis, Warburg effect and lipid metabolism. 45 Other derivatives appear less promising. 44,46 Dinuclear thiolatobridged arene ruthenium complexes are also promising as antiprotozoal agents, with IC50 values of up to 1.2 nM against T. gondii, N. Caninum and T. Brucei and IC50 values against human foreskin fibroblasts > 800 µM, leading to selectivity indexes > 20'000.…”
Section: Introductionmentioning
confidence: 99%